Investigating the anti-inflammatory properties of epigallocatechin gallate from green tea Camellia sinensis (L) O.Kuntze in mammalian innate immunity - Motshwene, Precious G. (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2020.